Topography of the synaptosomal membrane (The Rockefeller University Press, 1976)
The composition and disposition of the constituent polypeptides of rat cerebral cortical synaptosomal membranes were analyzed on SDS acrylamide gels. Of 20 bands readily detected, 11 account for greater than 93% of the total protein analyzed. These are: (molecu25); 3 (175); 4 (doublet, 137); 5 (doublet, 97); 6 (68); 7 (61); 8 (54); 9 (44); 10 (37); and 11 (33). Bands 5 and 8-10 are the most prominent and account for greater than 60% of the protein mass or 0.67 of its molecular fraction. By lactoperoxidase iodination, the bulk of the proteins in bands 3, 5, 6, and 8 and a portion of band 11 appear to be located on the external (junctional) face of the membrane of intact synaptosomes; proteins in bands 1, 2, 7, 9, and 10 appear to be localized on the internal (synaptoplasmic) face and become labeled only when synaptosomes are lysed. Further confirmation of the topographical distribution is provided by evidence that bands 3-6, 8, and 11 contain glycoproteins susceptible to labeling in intact synaptosomes by oxidation with galactose oxidase or periodate followed by reduction with NaB3H4. Evidence is provided for significant contributions by tubulin- and actin-like molecules to bands 8 and 9, respectively, suggesting that a substantial fraction of the tubulin in the synaptosomal membrane is disposed externally (accessible to iodination) whereas most, if not all, of the actin appears to exhibit the opposite topography. Similar though weaker inferences can also be drawn with regard to the location of tropomyosin and troponin. Preliminary evidence is provided that postsynaptic densities exhibit a protein and iodination profile distinct from that of the synpatosomal membrane.